The last noble gendarme : how the Tsar's last head of security and intelligence tried to avert the Russian Revolution - Marinich, Vladimir (Albany : State University of New York, 2021)
"Gripping account of the life of the Russian Tsar's last chief of security and intelligence"--
Beginnings -- Warsaw, Nizhni Novgorod, and Sevastopol -- As Petrograd's Chief of Security -- And Then, There Was the "Mad Monk" -- The Opportunists -- 1916, Leading to the End -- Turmoil and Arrest -- Sofia Springs into Action -- Incarceration -- Release, Fright, and Flight -- 1919 in Odessa -- Loss -- Constantinople -- Farewell to Constantinople -- The General's Last Assignment -- Toward the End.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 02, 2021).
JSTOR
Keywords: Globachev, K. I. -- 1870-1941.; Globacheva, Sofia Nikolaevna; Globachev family; Russia. -- Okhrannyi͡a otdi͡elenīi͡a -- Biography; Globachev family; Globachev, K. I. -- 1870-1941; Globacheva, Sofia Nikolaevna; Russia. -- Okhrannyi͡a otdi͡elenīi͡a; Secret service -- Russia -- History -- 20th century; Political culture -- Russia (Federation) -- Saint Petersburg -- History -- 20th century; Immigrants -- New York (State) -- New York -- Biography; Russians -- New York (State) -- New York -- Biography; Soviet Union -- History -- Revolution, 1917-1921.; Saint Petersburg (Russia) -- Biography; Service secret -- Russie -- Histoire -- 20e siècle.; Russes -- New York (État) -- New York -- Biographies; URSS -- Histoire -- 1917-1921 (Révolution); Immigrants; Political culture; Russians; Secret service; New York (State) -- New York; Russia; Russia (Federation) -- Saint Petersburg; Soviet Union; 1900-1999; Biographies; History